Gas-Permeable Membrane Technology Coupled With Anaerobic Digestion for Swine Manure Treatment - Molinuevo-Salces, Beatriz; Riaño, Berta; Vanotti, Matías B.; García-González, María C. (Frontiers in Sustainable Food Systems, 2018)
This study was aimed at evaluating gas-permeable membrane technology (N-recovery) coupled with anaerobic digestion (AD) for the treatment of swine manure (SM). For this purpose, 66.7% of the initial total ammoniacal nitrogen (TAN) contained in centrifuged SM was first recovered by an e-PTFE gas-membrane as an ammonium sulfate solution. The resultant manure effluent with reduced ammonia (ammonia-trapped manure, ATM) was evaluated as AD substrate. It was compared with AD using the initial swine effluent (SM) without the N-recovery step (control). An organic loading rate (OLR) of 2.8 ± 0.5 g total chemical oxygen demand (TCOD) L−1 day−1 was established to ensure a stable process when working at semi-continuous mode. Regardless of the operation mode, methane yields of 105 ± 2 mL CH4 g TCOD −1 were obtained for ATM. The combined treatment resulted in an organic matter removal efficiency of 68.6%. Initial TCOD accounted for 54.69 g L−1. The results prove that it is feasible to combine gas-permeable membrane technology and AD for the treatment of SM, contributing to ammonia emissions mitigation, and sustainable livestock waste treatment. Moreover, by means of this technology combination, a variety of valuable products is obtained, namely sustainable energy in the form of methane and fertilizers.